Spectrophotometric Assay of Phenylephrine hydrochloride in Pharmaceutical Formulation with Alizarin Red sulphonate in Aqueous Solution - Thabit Al-Ghabsha; A. Al-Delymi (College of Education for Pure Sciences, 2013)
ABSTRACT A simple, rapid and sensitive spectrophotometric method for the determination of phenylephrine hydrochloride was developed. The method is based on the proton transfer reaction with alizarin red sulphonate in aqueous neutral solution to form a violet product showing a maximum absorbance at 530 nm with molar absorptivity of 14320 l.mol-1.cm-1. The method is obeyed Beer's law over the concentration range (0.5-10) mg.ml-1. The accuracy (average recovery) of the method is 99.72% and the precision (RSD) of the method is less than 1.5%. The method was successfully applied for the determination of phenylephrine hydrochloride in pharmaceutical formulation as eye drops and the results were in good agreement with the standard addition procedure.